SFRP5-leptin ratio as a promising index in post-partum women with gestational diabetes mellitus - Kimber-Trojnar, Żaneta; Patro-Małysza, Jolanta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2019)
INTRODUCTION: Gestational diabetes mellitus (GDM) has often been referred to as the “marker” for the development of diabetes, obesity and cardiovascular diseases in future lives of women. In the current literature the adiponectin-leptin ratio is presented as a valuable index to estimate adipose tissue dysfunction. OBJECTIVES: The aim of the study was to investigate the significance of a novel parameter, i.e. the ratio of serum concentration of secreted frizzled-related protein 5 (SFRP5) to that of leptin in the early post-partum period. The associations between SFRP5/leptin ratio and maternal laboratory test results, body composition and hydration status were also assessed. PATIENTS AND METHODS: 26 mothers diagnosed with gestational diabetes mellitus (GDM) and 28 healthy controls were enrolled in the study. Body composition and hydration status of the patients were evaluated with the use of bioelectrical impedance analysis (BIA) method. The serum concentrations of SFRP5, leptin, fatty acid-binding protein 4 (FABP4) and ghrelin were determined via enzyme-linked immunosorbent assay (ELISA). RESULTS: SFRP5/leptin ratio was lower in the GDM mothers in comparison to that of the control group. There were positive correlations between SFRP5/leptin ratio and total cholesterol and low-density lipoprotein cholesterol (LDL) levels. The SFRP5/leptin ratio correlated negatively with total body water (TBW) and extracellular water (ECW). CONCLUSIONS: The SFRP5/leptin ratio appears to be a promising index for evaluating of metabolic disturbances in mothers with a history of GDM.